1995
DOI: 10.1037/0033-2909.117.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Sexual fantasy.

Abstract: This article reviews the research literature on sexual fantasy, a central aspect of human sexual behavior. Topics include (a) gender similarities and differences in the incidence, frequency, and content of sexual fantasies and how they relate to sociocultural and sociobiological theories of sexual behavior; (b) the association between frequency or content of sexual fantasies and variables such as age, sexual adjustment and satisfaction, guilt, sexual orientation, personality, and sexual experience; and (c) "de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
279
2
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(311 citation statements)
references
References 154 publications
16
279
2
14
Order By: Relevance
“…Specifically, we were not interested in sexual aggression per se but in the automatic compatibility of sex and aggression. For many individuals, aggression may be experienced as incompatible with sexual arousal whereas for others this is not the case (Leitenberg & Henning, 1995). The available evidence that sexual narcissists report greater frequencies of having used force to attain sexual gratification as well as a greater likelihood of using aggression to reach sexual satisfaction (Widman & McNulty, 2010) suggests that, for them, sexual arousal and aggression are less incompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we were not interested in sexual aggression per se but in the automatic compatibility of sex and aggression. For many individuals, aggression may be experienced as incompatible with sexual arousal whereas for others this is not the case (Leitenberg & Henning, 1995). The available evidence that sexual narcissists report greater frequencies of having used force to attain sexual gratification as well as a greater likelihood of using aggression to reach sexual satisfaction (Widman & McNulty, 2010) suggests that, for them, sexual arousal and aggression are less incompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the multicomponent nature of fantasy, researchers have also demonstrated that the content of sexual fantasy is highly dependent on what an individual reads, sees, hears, and directly experiences (Jones & Barlow, 1990;Leitenberg & Henning, 1995), and varies as a function of past experiences, cognitive style, personality, and an individual's level of creativity (Briere, Smiljanich, & Henschel, 1994;Mednick, 1977;Reich, 1993;Rokach, 1990). Four overarching content categories of sexual fantasy have been observed (Arndt et al, 1985;Crepault, Abraham, Porto, & Couture, 1976;Meuwissen & Over, 1991;Plaud & Bigwood, 1997;Smith & Over, 1987Wilson & Lang, 1981): conventional homosexual or heterosexual imagery with past, present, or imaginary lovers who are usually known to the person; scenes expressing sexual power and irresistibility; fantasies involving somewhat varied or "forbidden" sexual imagery; and submission-dominance scenes.…”
Section: Introductionmentioning
confidence: 99%
“…Four overarching content categories of sexual fantasy have been observed (Arndt et al, 1985;Crepault, Abraham, Porto, & Couture, 1976;Meuwissen & Over, 1991;Plaud & Bigwood, 1997;Smith & Over, 1987Wilson & Lang, 1981): conventional homosexual or heterosexual imagery with past, present, or imaginary lovers who are usually known to the person; scenes expressing sexual power and irresistibility; fantasies involving somewhat varied or "forbidden" sexual imagery; and submission-dominance scenes. Although there is uniformity in themes between the genders, males tend to endorse most fantasies at a higher rate than females (for a review see Leitenberg & Henning, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Research on masturbation (Gerressu, Mercer, Graham, Wellings, & Johnson, 2008), sexual fantasy (Leitenberg & Henning, 1995), frequency of thinking about sex, and desired number of sex partners supports this gender difference (Baumeister, Catanese, & Vohs, 2001). The Arousability factor has elements in common with the Excitation subscales (SES) from the SIS/SES measure (Janssen et al, 2002a), particularly the first subscale (social interactions) and third subscale (thinking and fantasizing about sex).…”
mentioning
confidence: 98%